2021
DOI: 10.1093/jscr/rjab455
|View full text |Cite
|
Sign up to set email alerts
|

A needle in the colon, the risk of ingested foreign objects: a case report

Abstract: Ingestion of foreign bodies is often found in clinical practice; however, intestinal perforation due to ingestion of foreign bodies is rare. Sharp and metallic objects are usually the ones that cause most complications. Preoperative diagnosis is difficult since the clinical presentation is vague and nonspecific presentation can simulate many abdominal pathologies. Patients are rarely aware of foreign body ingestion, and a high index of suspicion is required to make a timely diagnosis. In addition, treatment de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Ha et al [ 30 ] reported the case of a 34-year-old tailor who swallowed a sewing needle and, after an unsuccessful colonoscopy, underwent a laparoscopic appendectomy. Another publication by Espin et al [ 31 ] describes the case of a tailor who was diagnosed with colonic perforation after swallowing a needle and was treated surgically with a laparoscopic approach. To our knowledge, this is the first case report found in the literature of an endoscopic retraction of a sewing pin in a patient who is at occupational risk for ingestion—a tailor.…”
Section: Discussionmentioning
confidence: 99%
“…Ha et al [ 30 ] reported the case of a 34-year-old tailor who swallowed a sewing needle and, after an unsuccessful colonoscopy, underwent a laparoscopic appendectomy. Another publication by Espin et al [ 31 ] describes the case of a tailor who was diagnosed with colonic perforation after swallowing a needle and was treated surgically with a laparoscopic approach. To our knowledge, this is the first case report found in the literature of an endoscopic retraction of a sewing pin in a patient who is at occupational risk for ingestion—a tailor.…”
Section: Discussionmentioning
confidence: 99%
“…Incidental ingestion of a foreign body is a common problem [3] , and it could be critical and fatal [6] . The majority of cases before 1900 were woman holding pins and needles between their lips, and nowadays it happens mainly among children and adults with psychiatric conditions [3] , [7] . However, it can happen to anyone, as it happened to this patient.…”
Section: Case Presentationmentioning
confidence: 99%
“…After ingestion, the characteristics of the object determine whether it can perforate, progress to an obstruction or leave the body without complications. The intestine protects itself from perforation due to intrinsic ability; the mucosa enlarges the bowel wall at the point of contact, which leads to easier pass of the foreign body [3] . Nearly 80 to 90 % of swallowed foreign bodies evacuate via the rectum among healthy patients [9] .…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation